Alkaloids from the mangrove endophytic fungus Diaporthe phaseolorum SKS019. Issue 4 (15th February 2017) - Cui, Hui; Yu, Jianchen; Chen, Senhua; Ding, Meng; Huang, Xishan; Yuan, Jie; She, Zhigang
Graphical abstract: Abstract: Six new alkaloids including four new chromeno[3, 2-c]pyridines, diaporphasines A-D (1 –4 ), and two new isoindolinones, meyeroguillines C and D (6 –7 ), as well as three known compounds meyeroguilline A (5 ), 5-deoxybostrycoidin (8 ), and fusaristatin A (9 ), were isolated from an endophytic fungus Diaporthe phaseolorum SKS019. Their structures were determined by analysis of 1D and 2D NMR and mass spectroscopic data. Compounds1 –9 are alkaloid components reported for the first time from the Diaporthe sp., and diaporphasines A-D (1 –4 ) are the third examples of alkaloids possessing the unique chromeno[3, 2-c]pyridine nucleus . All isolated compounds1 –9 were evaluated for their cytotoxic activity in vitro using MDA-MB-435, HepG2, MCF10A, HCT116, and NCI-H460 human cell lines. Compound8 exhibited cytotoxicity against MDA-MB-435 and NCI-H460 human cancer cell lines with IC50 values of 5.32 and 6.57 μM, respectively, and compound9 showed growth-inhibitory activity against MDA-MB-435 human cancer cell line with IC50 value of 8.15 μM.